Sagot :
Answer:
(x + 2) and (x + 3)
Step-by-step explanation:
- Factoring:
f(x) = x² + 5x + 6
- Since x is the only variable we dont need to do much work.
- Find the factors of the last term that sums up to the coefficient of the middle term.
Last Term: 6
Factors of 6: (1 and 6), (2 and 3)
- Find the pair tht sums up to the middle coefficient.
Middle Coefficient: 5
Factors of 6 that sums to 5: (2 and 3)
- Hence the Factors are:
(x + 2) and (x + 3)
- Checking:
Use Foil Method:
(x + 2)(x + 3)
F = x • x = x²
O = x • 3 = 3x
I = 2 • x = 2x
L = 2 • 3 = 6
x² + 3x + 2x + 6
- Combine Like Terms
x² + 3x + 2x + 6
x² + 5x + 6
Therefore, the factors are (x + 2) and (x + 3)
#CarryOnLearning
#BetterAnswersAtBrainly
#BrainliestAnswers